Upaya Menumbuhkan Jiwa Kewirausahaan Melalui Program Sosialisasi Kewirausahaan Terhadap Siswa SD Negeri Kauman 2 Blitar - Andien Putri Amalia; Ratna Melinda Putri; Ula Farhah Nailah; Bagus Indra Kurniawan; Rafi Anggara Nindiaputra; Dewi Puspa Arum (Jurnal Pengabdian Kepada Masyarakat, 2023)
Based on survey results, school-age children generally lack an entrepreneurial spirit. Therefore, it is necessary to provide basic education regarding the importance of instilling an entrepreneurial spirit from an early age to students at SD Negeri Kauman 2. So that the expected solution from this dedication is to provide basic education and the benefits of having an entrepreneurial spirit. The method for this dedication activity is to use the Observation Method. The results achieved in this community dedication activity. First, there is awareness among students about the importance of entrepreneurship from an early age; Second, the development of students' creativity which is manifested in the form of handicrafts such as beads and tie dye batik. Third, students are inspired to do entrepreneurship as a form of appreciation for the results of their hands.